Thermophysical properties of methanol based Al2O3 nanofluids. (June 2015) - Mostafizur, R.M.; Saidur, R.; Abdul Aziz, A.R.; Bhuiyan, M.H.U.
Abstract: In this study, different volume concentrations (0.05, 0.10, 0.15, 0.20 and 0.25 vol%) of cylindrical shaped Al2 O3 nanoparticles (50 nm length and 8 nm diameter) were suspended in methanol to produce methanol based nanofluid (MBNF). The nanofluid was prepared by using an ultrasonic homogenizer without any surfactants. Thermal conductivity ( k ), viscosity ( μ ), density ( ρ ) and specific heat ( Cp ) of the nanofluid were measured for a wide range of temperatures (5, 10, 15, 20 and 25 °C). The k values in the range of 0.207–0.234 W/mK, μ values in the range of 0.70–0.94 mPas, ρ values in the range of 791–814 kg/m 3 and Cp values in the range of 1.024–1.416 J/g °C were observed as the volume concentration increased from 0.05 to 0.25 vol% with the temperature rising from 5 to 25 °C. The results showed that thermal conductivity, viscosity and density increased while specific heat decreased with increase in Al2 O3 particle concentration. Besides, thermal conductivity and specific heat increased while viscosity and density decreased with increase in temperature.